If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1 = 4x + 2 Reorder the terms: 1 + 2x = 4x + 2 Reorder the terms: 1 + 2x = 2 + 4x Solving 1 + 2x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + 2x + -4x = 2 + 4x + -4x Combine like terms: 2x + -4x = -2x 1 + -2x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + -2x = 2 + 0 1 + -2x = 2 Add '-1' to each side of the equation. 1 + -1 + -2x = 2 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 2 + -1 -2x = 2 + -1 Combine like terms: 2 + -1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5
| n^3+3n^2+3n+2=0 | | 7x-14=-9 | | 2(x+5)+3(x-2)=64 | | 4x^3+15x^2+3x+28=0 | | 4x^2+15x+3=0 | | 2x*5y=50 | | -5/16/25/8= | | 5/8-(1/2-3/4)= | | 10(-3+-2t)+10+-2(6t+-13)=0 | | x(x^2-9)=0 | | 10(-3-2t)+10-2(6t-13)=3 | | -0.2x^2+0.1x=-0.06 | | -5z^2-4z+3=0 | | 4(64)+12=0 | | -18x+4y=74 | | X+x-3+x+5=35 | | x(x^2-25)=0 | | 5(x-6)+6=7x-6 | | X+(x+5)+(x-3)=35 | | x(x+5)(x-1)=0 | | 6-6x=5x-8x+15 | | x^2+y^2+z=1 | | 5(6y-4)+19=3(4y+4)+7 | | 3(2y-4)+18=4(3y+1)+1 | | x^2+y^2-z=1 | | 7x-3=2x-5 | | 14x-20-13x=-14 | | 6x+7x-76=95-6x | | 105=(p^2-p) | | -18x-13=15x-4 | | x^2-37x-120=0 | | s=(p^2-p) |